2005
DOI: 10.1164/rccm.200506-953oc
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9 Promoter Polymorphism Associated with Upper Lung Dominant Emphysema

Abstract: Polymorphism of MMP-9 (C-1562T) was associated with upper lung dominant emphysema in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 47 publications
0
108
1
2
Order By: Relevance
“…Thus, MMP-9 is involved in the deterioration of components of the extracellular matrix such as gelatin, the collagens (IV, V, XI and XVII) and elastin. It has been shown that a polymorphism of MMP-9 (C-1562T) is associated with upper lung dominant emphysema [50,51]. In addition, a genetic predisposition for proteolysis of elastin in connection with the expression of a variant of the terminal exon in human elastin has been described for patients with severe COPD [52].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Thus, MMP-9 is involved in the deterioration of components of the extracellular matrix such as gelatin, the collagens (IV, V, XI and XVII) and elastin. It has been shown that a polymorphism of MMP-9 (C-1562T) is associated with upper lung dominant emphysema [50,51]. In addition, a genetic predisposition for proteolysis of elastin in connection with the expression of a variant of the terminal exon in human elastin has been described for patients with severe COPD [52].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Family studies confirm there is a heritable component of COPD 41 . Using a candidate gene approach with assumptions about the pathogenic mechanisms, polymorphisms in multiple genes with putative relevance to COPD have been identified in small studies, including microsomal epoxide hydroxylase (EPHX1) 6,7,40,42 , angiotensin converting enzyme 43,44 , β-defensin 1 45,46 , glutathione Stransferase 42,47 , matrix metalloproteinases 48,49 and tumor necrosis factor 50,51 . However, follow up studies in wider population have sometimes failed to confirm these association, possibly due to there likely being multiple genes associated with susceptibility/resistance to COPD, which may not be equally influential in all populations [11][12][13][14] .…”
Section: Implication Of Airway Gene Expression Variability For Genesimentioning
confidence: 99%
“…Several polymorphisms potentially affecting gene expression have been described in promoter regions of MMPs genes (Table 1). In a recent Japanese study the importance of MMP-9 gene -1562C/T promoter polymorphism in the development of pulmonary emphysema in Japanese smokers was suggested (Minematsu et al 2001) and this was reported again in another recent Japanese study (Ito et al 2005). In Caucasians, Joos et al (2002a) showed that the MMP-1 gene G-1607GG promoter polymorphism and the MMP-12 gene Asn357Ser polymorphism in the coding region were associated with the rate of decline in lung function in continuing smokers.…”
Section: Gene Polymorphisms Of Matrix Metalloproteinases In Copdmentioning
confidence: 87%